Pengaruh Kreativitas Guru Terhadap Efikasi Diri Peserta Didik Dalam Belajar Matematika Di Kecamatan Kebomas - Maf'ula, Iswatun; Edy, Sarwo; Suryanti, Sri (Universitas Muhammadiyah Gresik, 2025)
Abstract Perceptions of a lack of Teacher innovation in presenting the content in PLP 2 led some students to feel bored and uninterested in learning, which in turn spurred this research. Furthermore, several students were uncertain of their own replies to the teacher's questions and opted to check or match the answers provided by their classmates before responding. As a result, the researcher in Kebomas District set out to determine how students' perceptions of their own mathematical abilities were affected by teachers' levels of creativity in the classroom. Finding out how teachers' imaginations affect their pupils' confidence in their own mathematical abilities was the overarching goal of this research. Two hundred forty-six children from Kebomas District's seventh and eighth grade classes participated in the study. This study is a survey-based correlational analysis. The study found that students' self-efficacy in math learning is influenced by a total of 91.5% of the variables not included in this study, with 8.5% of that influence coming from teachers' creativity in the areas of classroom atmosphere, asking questions, innovative teaching practices, overcoming obstacles, and teaching style. As a result, the researcher in Kebomas District set out to determine how students' perceptions of their own mathematical abilities were affected by teachers' levels of creativity in the classroom. Finding out how teachers' imaginations affect their pupils' confidence in their own mathematical abilities was the overarching goal of this research. Two hundred forty-six children from Kebomas District's seventh and eighth grade classes participated in the study. This study is a survey-based correlational analysis. Teachers' confidence in themselves as educators, the quality of their classroom environments, their ability to help students overcome challenges, the frequency with which they ask questions, and the innovative practices they employ all have an impact on students' perceptions of their own mathematical abilities; however, other factors beyond the scope of this study account for the remaining 91.5% of the variation in students' perceptions of their own mathematical abilities. Abstrak Persepsi tentang kurangnya inovasi guru dalam menyajikan konten dalam PLP 2 menyebabkan beberapa siswa merasa bosan dan tidak tertarik dalam belajar, yang pada gilirannya memacu penelitian ini. Lebih jauh, beberapa siswa tidak yakin dengan jawaban mereka sendiri terhadap pertanyaan guru dan memilih untuk memeriksa atau mencocokkan jawaban yang diberikan oleh teman sekelas mereka sebelum menjawab. Akibatnya, peneliti di Distrik Kebomas berusaha untuk menentukan bagaimana persepsi siswa tentang kemampuan matematika mereka sendiri dipengaruhi oleh tingkat kreativitas guru di kelas. Mencari tahu bagaimana imajinasi guru memengaruhi kepercayaan diri murid-murid mereka terhadap kemampuan matematika mereka sendiri adalah tujuan utama dari penelitian ini. Dua ratus empat puluh enam anak dari kelas tujuh dan delapan Distrik Kebomas berpartisipasi dalam penelitian ini. Penelitian ini adalah analisis korelasional berbasis survei. Penelitian ini menemukan bahwa efikasi diri siswa dalam pembelajaran matematika dipengaruhi oleh total 91,5% variabel yang tidak termasuk dalam penelitian ini, dengan 8,5% pengaruh tersebut berasal dari kreativitas guru dalam bidang suasana kelas, mengajukan pertanyaan, praktik mengajar yang inovatif, mengatasi rintangan, dan gaya mengajar. Hasilnya, peneliti di Kabupaten Kebomas berupaya untuk menentukan bagaimana persepsi siswa terhadap kemampuan matematika mereka sendiri dipengaruhi oleh tingkat kreativitas guru di kelas. Mencari tahu bagaimana imajinasi guru memengaruhi kepercayaan diri siswa terhadap kemampuan matematika mereka sendiri adalah tujuan utama penelitian ini. Dua ratus empat puluh enam anak dari kelas tujuh dan delapan Kabupaten Kebomas berpartisipasi dalam penelitian ini. Penelitian ini merupakan analisis korelasional berbasis survei. Kepercayaan diri guru terhadap diri mereka sendiri sebagai pendidik, kualitas lingkungan kelas mereka, kemampuan mereka untuk membantu siswa mengatasi tantangan, frekuensi mereka mengajukan pertanyaan, dan praktik inovatif yang mereka terapkan semuanya berdampak pada persepsi siswa terhadap kemampuan matematika mereka sendiri; Namun, terdapat faktor lain di luar cakupan penelitian ini yang menyebabkan 91,5% variasi persepsi siswa terhadap kemampuan matematika mereka sendiri.